Cell therapy of critical limb ischemia in diabetic patients - State of art - Dubský, Michal; Jirkovská, Alexandra; Bem, Robert; Nemcová, Andrea; Fejfarová, Vladimira; Jude, Edward B (Diabetes research and clinical practice, 2017)
In this review we report on the state of cell therapy of critical limb ischemia (CLI) with respect to differences between diabetic and non-diabetic patients mainly from the clinical point of view. CLI is the most severe form of peripheral arterial disease and its diagnosis and treatment in diabetic patients is very difficult. The therapeutic effect of standard methods of CLI treatment is only partial - more than one third of diabetic patients are not eligible for standard revascularization; therefore, new therapeutic techniques such as cell therapy have been studied in clinical trials. Presence of CLI in patients with diabetic foot disease is associated with worse clinical outcomes such as lack of healing of foot ulcers, major amputations and premature mortality. A revascularization procedure cannot be successful as the only method in contrast to patients without diabetes, but it must always be part of a complex therapy focused not only on ischemia, but also on treatment of infection, off-loading, metabolic control of diabetes and nutrition, local therapy, etc. Therefore, the main criteria for cell therapy may vary in diabetic patients and non-diabetic persons and results of this treatment method should always be assessed in the context of ensuring comprehensive therapy. This review carries out an analysis of the source of precursor cells, route of administration and brings a brief report of published data with respect to diabetic and non-diabetic patients and our experience with autologous cell therapy of diabetic patients with CLI. Analysis of the studies in terms of diabetes is difficult, because in most of them sub-analysis for diabetic patients is not performed separately. The other problem is that it is not clear if diabetic patients received adequate complex treatment for their foot ulcers which can strongly affect the rate of major amputation as an outcome of CLI treatment.
Keywords: Diabetic Foot; Critical limb ischemia; Foot Ulcer; hojení ran; lidé; Middle Aged; Wound Healing; Cell therapy; Diabetic Angiopathies; vředy na noze (od hlezna dolů); diabetické angiopatie; Female; diabetická noha; amputace; Humans; Cell- and Tissue-Based Therapy; Diabetes mellitus; ischemie; Peripheral Arterial Disease; lidé středního věku; Ischemia; mužské pohlaví; buněčná a tkáňová terapie; ženské pohlaví; Amputation, Surgical; Male; Limb Salvage; záchrana končetiny; onemocnění periferních arterií